Antibacterial of Eight Macrofungi Species Against - Noverita Noverita; Nyoman Ayu Ratmini (Journal of Tropical Biodiversity, 2022)
Indonesia is a newly developing country, with many problems, one of which is health problems related to medicinal ingredients (antibiotics). Many microorganisms, especially bacteria, are resistant to various types of antibiotics. Various efforts have been made by the government to find new antibiotics, to reduce the use of semisynthetic or synthetic antibiotics which are very dangerous. One of them uses macrofungi.The antibacterial activity of eight species of macrofungi (Ganoderma applanatum, G. boninense, Ganoderma sp1, Ganoderma sp2, Trametes sp1, Trametes sp2, Trametes sp3, Microporus xanthopus and Suillus sp1) against Escherichia coli and Staphylococcus aureus has been carried out, using the diffusion method. The results showed that six species were able to inhibit the growth of Staphylococcus aureus. The species were Ganoderma applanatum, Ganoderma sp1, Trametes sp.1, Trametes sp.2, Trametes sp.3, and Suillus sp. The resulting limiting zone ranged from 6.5-11 mm. The zone of inhibition produced by Trametes, the smallest inhibition zone of Ganoderma sp1. The higher the concentration of the extract, the greater the ability to inhibit the growth of the test bacteria.